Pterygodermatites (Mesopectines) whartoni (Nematoda: Rictulariidae) encysted larvae in invasive Cuban treefrogs (Osteopilus septentrionalis) from Florida, United States - Lykins, Kelsey; Ossiboff, Robert J.; Chase, Ellis; Thompson, Nina; Farrell, Terence M.; Wu, Timothy; Johnson, Steve A.; Walden, Heather D. S. (Frontiers in Veterinary Science, 2024)
Species of Pterygodermatites are spirurid nematodes that have expanded their geographic distribution worldwide. They infect a variety of mammalian definitive hosts with few reports of potential paratenic infections in amphibian and reptile hosts. In this study, we report Pterygodermatites sp. larvae identified in free-ranging, invasive Cuban treefrogs (Osteopilus septentrionalis), from central Florida, USA. Encysted larvae were recovered from the skeletal muscle and/or the coelomic cavity of three frogs; molecular characterization of the small subunit (18S) ribosomal RNA and cytochrome oxidase I genes of the parasites matched reported sequences of Pterygodermatites (Mesopectines) whartoni (Tubangui, 1931). This is a parasite native to Southeastern Asia and to the best of the authors' knowledge, it is the first report of the species in the New World. The recovery of invasive Pterygodermatites from invasive Cuban treefrogs in North America highlights the growing concern regarding the potential impact non-native parasites and invasive species may have on native wildlife populations.